The Politics of Vocational and Technical Education Curriculum: An Analysis of the Implementation of Vocational and Technical Education in Zimbabwe - Sisimayi, Gideon Wilson; Chikasha, Dr. Adolph Silas (IJRDO- Journal of Educational Research, 2016)
The study sought to analyse pre-colonial era system of vocational and technical education in Zimbabwe in contrast with the post-independence period. It defined Curriculum and Politics in educational issues. The paper looked at the hurdles in the implementation of vocational and technical education, citing human interests and attitudes towards vocational and technical education. The study used the interpretivist methodology based on the case study survey design. Open ended in-depth interviews were used to gather data. The study found that there was no real and clear government policy on vocational and technical education in Zimbabwe’s education system except in theory and on paper. It concluded that it would take decades and decades before true vocationalisation found its way into the country’s education system. The following were the main recommendations: Government should appoint a panel of educationists to formulate policy on vocational and technical education in Zimbabwe. Ministry of Finance should set aside adequate funds to implement vocational and technical education programmes.